Developing a green film with pH-sensitivity and antioxidant activity based on к-carrageenan and hydroxypropyl methylcellulose incorporating Prunus maackii juice. (September 2019) - Sun, Guohou; Chi, Wenrui; Zhang, Cijian; Xu, Shiyu; Li, Jian; Wang, Lijuan
Abstract: A green film with pH-sensitivity and antioxidant activity based on к-carrageenan and hydroxypropyl methylcellulose incorporating Prunus maackii juice was prepared in this experiment. The addition of P. maackii juice enhanced the tensile strength, compactness, barrier, and antioxidant activity of the film. With increasing juice content, the elongation at break of the film can reach 48.64 ± 4.94%, and the antioxidant activity can reach 28.76 ± 0.61%. The minimum oxygen permeability was 1.63 ± 0.09 cm 3 mm m −2 day −1 atm −1 and the minimum water vapor permeability was 0.37 ± 0.01 g m −1 s −1 Pa −1 × 10 −12 . Oxidation of lard sealed in the film packaging was inhibited. The films are more effective for slowing the oxidation of lard than commercial PE film. The color of the film changed from deep red to blue-gray when the pH was increased from 3 to 13. Thermogravimetric analysis showed that addition of the juice had no significant effect on the thermal stability of the film. The film changed from red to blue when the volatile base nitrogen content in the pork was 19.26 ± 0.84 mg/100 g. The green film with P. maackii juice can be used both for oil packaging and as a label for testing pork freshness. Graphical abstract: Image 10162 Highlights: Films were prepared from κ-carrageenan and HPMC incorporating Prunus maackii juice. The addition of P. maackii juice affected the barrier properties of the film. The film showed the pH sensitivity and antioxidant activity. The color of the film changed from red to blue as pork spoil occurred.